2018
DOI: 10.15625/2525-2518/54/2c/11863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfation on the Structure and Anticoagulant Activity of Ulvan Extracted From Green Seaweed Ulva Reticulata

Abstract: Ulvans are sulfated polysaccharides derived from the cell wall of green seaweeds. The chemical structure of ulvan extracted from Ulva reticulata is reported, focusing on investigation of the sulfated modification of the ulvan and the changes in structure and anticoagulant activity. The results showed that sulfated modification was able to change the ulvan conformational structure and markedly enhance its anticoagulant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thus, the degree of sulfation does not seem to be the only parameter affecting the anticoagulant activity of ulvans. Other polyanionic polysaccharides from various origins have been shown to have an anticoagulant activity strongly related to their degree of sulfation ([43,44,46,47]: sulfated fucans, in particular, have been extensively studied and their activity has been proved to be mainly mediated by thrombin inhibition by either antithrombin or heparin cofactor II, at different extents. However, numerous studies on sulfated fucans and galactans [60,61,62], and more recently on carrageenans [63], also established that anticoagulant activity, particularly in terms of efficiency, is not merely a function of charge density and depends critically on other structural features [46,47]: monosaccharide composition, glycosidic bounds, MW [50], branching residues, and position of sulfate groups on the sugar backbone [18,60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the degree of sulfation does not seem to be the only parameter affecting the anticoagulant activity of ulvans. Other polyanionic polysaccharides from various origins have been shown to have an anticoagulant activity strongly related to their degree of sulfation ([43,44,46,47]: sulfated fucans, in particular, have been extensively studied and their activity has been proved to be mainly mediated by thrombin inhibition by either antithrombin or heparin cofactor II, at different extents. However, numerous studies on sulfated fucans and galactans [60,61,62], and more recently on carrageenans [63], also established that anticoagulant activity, particularly in terms of efficiency, is not merely a function of charge density and depends critically on other structural features [46,47]: monosaccharide composition, glycosidic bounds, MW [50], branching residues, and position of sulfate groups on the sugar backbone [18,60].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the anticoagulant activity, the most studied genera are Codium [31,32,33,34,35,36], which contains sulfated arabinans and arabinogalactans, and then Monostroma , which contains sulfated rhamnans [37,38,39,40,41,42]. Only two studies have shown the potential anticoagulant properties of ulvans extracted from Ulva conglobata and Ulva reticulata [43,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained by these authors also indicate that the PS fractions from different types and species of brown algae, enriched with sulfates, but poor with uronic acids, exhibit relatively high activity, while the fractions with the inverse ratio of these structural components have a weaker anticoagulant activity. As for PSs from different types of green algae, it also was demonstrated that high-molecular-weight sulfated galactans with a high content of sulfates have a higher anticoagulant activity than low-molecular-weight PSs with a low content of sulfates [ 31 , 32 , 33 ].…”
Section: Anticoagulant Antithrombotic and Fibrinolytic Activities Of Seaweed Sulfated Polysaccharidesmentioning
confidence: 99%